2020
DOI: 10.1097/sla.0000000000003010
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatectomy With Arterial Resection for Pancreatic Adenocarcinoma: How Can It Be Done Safely and With Which Outcomes?

Abstract: In a specialized setting, P-AR for locally advanced pancreatic adenocarcinoma can be performed safely with limited mortality and morbidity. Negative resection margin and the absence of associated venous invasion might predict favorable long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 64 publications
5
81
1
2
Order By: Relevance
“…Another kind of patient the PAMG could impact are the 20 to 30% percent of patients diagnosed with a locallyadvanced disease. If pancreatectomy and simultaneous arterial resection has traditionally been considered as a general contraindication to resection [19], some of these patients with good prognosis might indeed benefit from aggressive surgical approaches [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another kind of patient the PAMG could impact are the 20 to 30% percent of patients diagnosed with a locallyadvanced disease. If pancreatectomy and simultaneous arterial resection has traditionally been considered as a general contraindication to resection [19], some of these patients with good prognosis might indeed benefit from aggressive surgical approaches [20].…”
Section: Discussionmentioning
confidence: 99%
“…After 3 passages, tumors were isolated and RNA extracted using the miRneasy mini kit (Qiagen). RNA-seq was performed as previously described [9,20] using Illumina's TrueSeq Stranded RNA LT protocol to obtain 100b paired-end reads. RNA-seq reads were mapped using STAR and SMAP on the human hg19 and mouse mmu38 genomes.…”
Section: Pacaomics Patient Derived Tumor Xenograft and Rna-sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the Mayo Clinic group (24,120) and Bachellier et al (121) reported more than 100 ARs (LE 4). In 2018, the Mayo Clinic group reported results in 111 patients who underwent pancreatectomy with AR [HA (n = 60), celiac (n = 49), SMA (n = 15), multiple ARs (n = 15)] including 55% with reconstruction and 51% with simultaneous VRs (120).…”
Section: Commentsmentioning
confidence: 99%
“…Bachellier et al (121) reported 118 pancreatectomies (51 PD, 18 TP, and 49 DP) with ARs [CA (50), HA (29), SMA (35), and other segments (4)] including 85% with reconstruction and 89% with simultaneous VR (LE 4). Overall mortality and morbidity were 5.1 and 41.5%, respectively.…”
Section: Commentsmentioning
confidence: 99%